2022
DOI: 10.1177/03611981221091551
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of IDEAL-CT Device Equivalence: Are All Devices Equal?

Abstract: The IDEAL-CT (InDirect tEnsile AsphaLt Cracking Test) has rapidly become a popular cracking test for asphalt mixture acceptance. There have been several studies conducted to ensure this test is sufficient and acceptable for mixture acceptance purposes with respect to testing variability and the test’s ability to detect mixture quality improvements. A potential source of testing variability yet to be comprehensively studied is the variability introduced between testing devices. This paper provides a case study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Newcomb et al ( 7 ) evaluated several Minnesota asphalt mixtures from projects constructed in 2018 and found that the time between sample molding and testing could vary by as much as two weeks without affecting the IDT-CT results. Moore et al ( 8 ) evaluated the effect of test devices by considering five unique loading frames and an independent data acquisition system mounted on one of the frames using seven asphalt mixtures. One device was operating differently enough from the other five that results could not be considered equivalent; for the other five devices, the results were equivalent.…”
mentioning
confidence: 99%
“…Newcomb et al ( 7 ) evaluated several Minnesota asphalt mixtures from projects constructed in 2018 and found that the time between sample molding and testing could vary by as much as two weeks without affecting the IDT-CT results. Moore et al ( 8 ) evaluated the effect of test devices by considering five unique loading frames and an independent data acquisition system mounted on one of the frames using seven asphalt mixtures. One device was operating differently enough from the other five that results could not be considered equivalent; for the other five devices, the results were equivalent.…”
mentioning
confidence: 99%